Cattle producers’ perceptions of biosecurity - Brennan, Marnie L.; Christley, Robert M. (BioMed Central, 2013)
Background: The limited use of biosecurity practices by many in the farming community is likely to be due to a range of factors; further understanding of this issue is required. In this study, attitudes and behaviours of producers relating to selected biosecurity practices and the farming industry were studied by interviewing cattle farmers within a 100 km2 study area in north-west England using an interview-based questionnaire. Results: Most producers appeared to be familiar with the broad concept of the term biosecurity, although risks due to indirect contacts, rather than direct (animal) contacts, were more frequently highlighted. Most producers felt the nominated biosecurity practices were in some way useful, however there was not always agreement between the usefulness of a practice and it being undertaken, and vice versa. In agreement with other studies conducted in the UK, farmers most preferred to obtain information and advice on biosecurity from private veterinarians, but also highlighted DEFRA as a source. Conclusions: This study highlights the importance of understanding the motivators and barriers behind the uptake of biosecurity practices on farms, as perceptions are variable. Further understanding of these issues is needed in order to more effectively communicate information in regards to herd health and disease prevention. By identifying differences in producers’ attitudes, programs can be tailored specifically to individuals’ needs.